Formation and mitigation of PCDD/Fs in iron ore sintering - Ooi, Tze Chean; Lu, Liming (Chemosphere (Oxford), 2011)
► Formation mechanism, congener distribution, contributing factors and mitigation strategies. ► Mode of action and merits of potential inhibiting compounds. ► Developments in PCDD/F downstream abatement strategies. The sintering of iron ore is presently a significant industrial source of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) worldwide owing to the fundamental requirement of the operation of a high temperature process to pre-treat fines and to recycle plant by-products arising from the integrated iron and steelworks. The process is a noteworthy contributor of PCDD/F indirectly due to decreasing PCDD/F releases from municipal solid waste incineration. Commonly PCDD/F formation from the process is associated with the addition of oily mill scales although raw material containing a combination of C, Cl and specific metal catalyst has been shown to drastically increase PCDD/F formation in the process. The degenerate graphitic structure of carbon present in coke fuel and soot formed and the chemistry of catalytic metals and Cl are important factors. A review on PCDD/F emission in this process has been carried out, including examination of its formation mechanism, congener distribution, contributing factors and mitigation strategies, with emphasis on the use of inhibiting compound to achieve suppression. A detailed analysis of the de novo and precursor theories of formation and the contributing factor is given since the subject of PCDD/F formation is still controversial. The de novo formation pathway identified in sinter plants and controlled studies performed in the laboratory as well as at pilot-scale are discussed; where appropriate, a comparison is drawn between sintering and other thermal processes emitting PCDD/Fs. Summary of the latest developments in PCDD/F downstream abatement strategies presently employed in full scale industrial plants is provided. Potential inhibiting compounds are discussed in terms of their mode of action and merits under sintering conditions.